Controlling self, facing the future: A study of the relationship between self-control and future orientation - Yanuar, Rizqi; Matulessy, Andik; Pratitis, Nindia (Institute of Computer Science (IOCS), 2025)
Dropping out of school is a worrying conflict for the nation's successors which is often done by students in the school environment. Based on the village classification, there is a difference between education in urban and rural areas. Students who do not have a future orientation are more likely to experience poor academic achievement. If students have a future orientation, they have a spirit of achievement, making them less likely to engage in deviant behavior. This study uses a quantitative method with a correlational research approach through sampling using the purposive sampling method, with test results using the product moment test. The purpose of this study is to identify the relationship between the presence or absence of self-control with future orientation in junior high school students in the coastal area of Tlocor. The results of the normality test of the distribution of self-control with future orientation against the One-Sample Kolmogorov Smirnov Test obtained sig 0.200 at (p> 0.05) it can be assumed that the distribution of the self-control scale with future orientation is normally distributed. The results of the hypothesis test using the product moment correlation processed using the IBM SPSS 25 for Windows program obtained an rxy score of 0.683 with sig. 0.000 (p<0.01) which can be interpreted as there is a very significant positive relationship between self-control and future orientation. This means that the higher the self-control, the more positive the future orientation of junior high school students.